COMPARATIVE STUDY OF JOB STABILITY OF TEACHERS WORKING IN SUBSIDIZED AND PRIVATE B.ED. INSTITUTIONS - Panwar, Shubham; Singh, Bindu (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Job stability is an important factor affecting the quality of personal, social and professional life of any teacher. This study attempts to understand the difference in service conditions, pay scale, appointment process, promotion prospects and job satisfaction of teachers working in both types of institutions and to what extent this difference affects their job stability. Teachers working in subsidized B.Ed. institutions generally get the benefit of rules laid down by the government, recommendations of the Pay Commission, permanent appointments and facilities like pension, due to which their job stability is relatively higher. In contrast, teachers working in private institutions often have to face low salaries, temporary contracts, uncertain service conditions and arbitrariness of the top management, which negatively affects their job stability. In this research, it was also observed that teachers working in aided institutions feel more confident, satisfied and secure, whereas teachers working in private institutions feel worried, dissatisfied and insecure about the future. Due to this, their dedication to work, tendency to innovation and teaching quality are also affected. Apart from this, the activeness of teachers' unions, service security system and judicial protection in aided institutions also prove to be helpful in maintaining job stability. On the other hand, in private B.Ed. institutions, the arbitrary behaviour of managers, termination of service from time to time and the process of reconfirmation of services destabilize the mental state of teachers. They are constantly worried about saving their jobs, due to which they are not able to give full attention to teaching work. This instability also affects the quality of students and the reputation of the institutions. Hence, it is clear that job stability is relatively more in aided B.Ed. institutions, whereas this stability is weak in private institutions.